Shedding of APP limits its synaptogenic activity and cell adhesion properties - Stahl, Ronny; Schilling, Sandra; Soba, Peter; Rupp, Carsten; Hartmann, Tobias; Wagner, Katja; Merdes, Gunter; Eggert, Simone; Kins, Stefan (Frontiers in Cellular Neuroscience, 2014)
The Amyloid precursor protein (APP) plays a central role in Alzheimer’s disease (AD) and has essential synapse promoting functions. Synaptogenic activity as well as cell adhesion properties of APP presumably depend on trans-cellular dimerization via its extracellular domain. Since neuronal APP is extensively processed by secretases, it raises the question if APP shedding affects its cell adhesion and synaptogenic properties. We show that inhibition of APP shedding using cleavage deficient forms of APP or a dominant negative α-secretase strongly enhanced its cell adhesion and synaptogenic activity suggesting that synapse promoting function of APP is tightly regulated by α-secretase mediated processing, similar to other trans-cellular synaptic adhesion molecules.